Presentasi diri influencer dalam product endorsement di instagram - Irnando, Kautsar; Irwansyah, irwansyah (Faculty of Communications Science, Dr. Soetomo University, 2021)
Transformation of technology has developed a new place for business activity known as social commerce, where Instagram has become the most popular social commerce. In promoting products through social media, mereks often use endorsers in product endorsement. Macro influencers who have broad audience range and unique self-presentation are proven to give positive impact towards product endorsement. The effectiveness leads to a new question, how do macro influencers present themselves in a product endorsement post? This research is conducted to answer that question. The method that is used in this research is a qualitative method to identify influencer self-presentation in product endorsement. Results of this research shows that influencers do not use a different self-presentation in product endorsement. The influencer put the endorsement strategy on their post. Another finding shows that mereks have some deals in self-presentation of influencers within a product endorsement post.